2022
DOI: 10.1002/pbc.29763
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and 5‐year survival of children and adolescents with hepatoblastoma in the United States

Abstract: Objective: Hepatoblastoma (HB) is the most common pediatric primary malignant liver tumor, its incidence has been increasing worldwide, but recent changes in incidence and outcomes with high population coverage are not well characterized. Methods: We defined the incidence of HB diagnosed during 2003-2017 from United States Cancer Statistics (USCS) database, and survival during 2001-2016 from the National Program of Cancer Registries (NPCR). Data were stratified by sex, race/ethnicity, age, tumor stage, county … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Whereas radiological parameters in PRETEXT/POSTTEXT system have proved to be prognostic for patient outcomes (37)(38)(39), there aren't much option for laboratory biomarkers. AFP is currently the only serum biomarker of HB that universally utilized for diagnosis and outcome prediction (39,40). AFP contributes to the backbone groups of global risk stratification system of HB (7).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas radiological parameters in PRETEXT/POSTTEXT system have proved to be prognostic for patient outcomes (37)(38)(39), there aren't much option for laboratory biomarkers. AFP is currently the only serum biomarker of HB that universally utilized for diagnosis and outcome prediction (39,40). AFP contributes to the backbone groups of global risk stratification system of HB (7).…”
Section: Discussionmentioning
confidence: 99%
“…1 However, the incidence of hepatoblastoma has been increasing worldwide. 2 Most cases occur in children less than 5 years old. Adult cases are very rare with fewer than 70 adult cases reported in the literature.…”
Section: Hepatoblastomamentioning
confidence: 99%
“…9 The 5-year survival of hepatoblastoma has dramatically increased from 30% reported in the 1980s to approximately 75 to 90% reported in contemporary studies reflecting improvements in pretreatment staging, chemotherapy, surgical techniques, and introduction of liver transplantation for unresectable disease. 2…”
mentioning
confidence: 99%
“…In recent years, there has been an increasing amount of literature on the incidence and screening of the prognostic factors in HB, HCC, and ES among children and adolescents. Up to now, Justin’s study has indicated that HB incidence increased, meanwhile, age, race or ethnicity, and stage were the prognostic factors in 5-year relative survival ( 5 ). HCC is the second most common primary liver malignancy in a pediatric setting, which is diagnosed more commonly in adolescents (10–14 years).…”
Section: Introductionmentioning
confidence: 99%